Impact of exercise on pulmonary artery pressure in patients with heart failure using an ambulatory pulmonary artery pressure monitor - Khedraki, Rola; Abraham, Jacob; Jonsson, Orvar; Bhatt, Kunjan; Omar, Hesham R.; Bennett, Mosi; Bhimaraj, Arvind; Guha, Ashrith; McCann, Patrick; Muse, Evan D.; Robinson, Monique; Sauer, Andrew J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background In this multicenter prospective study, we explored the relationship between pulmonary artery pressure (PAP) at rest and in response to a 6-min walk test (6MWT) in ambulatory patients with heart failure (HF) with an implantable PAP sensor (CardioMEMS, Abbott). Methods Between 5/2019 and 2/2021, HF patients with a CardioMEMS sensor were recruited from seven sites. PAP was recorded in the supine and seated position at rest and in the seated position immediately post-exercise. Results In our cohort of 66 patients, mean age was 70 ± 12 years, 67% male, left ventricular ejection fraction (LVEF) < 50% in 53%, mean 6MWT distance was 277 ± 95 meters. Resting seated PAPs were 31 ± 15 mmHg (systolic), 13 ± 8 mmHg (diastolic), and 20 ± 11 mmHg (mean). The pressures were lower in the seated rather than the supine position. After 6MWT, the pressures increased to PAP systolic 37 ± 19 mmHg (p < 0.0001), diastolic 15 ± 10 mmHg (p = 0.006), and mean 24 ± 13 mmHg (p < 0.0001). Patients with elevated PAP diastolic at rest (>15 mmHg) demonstrated a greater increase in post-exercise PAP. Conclusion The measurement of PAP with CardioMEMS is feasible immediately post-exercise. Despite being well-managed, patients had severely limited functional capacity. We observed a significant increase in PAP with ambulation which was greater in patients with higher baseline pressures.